Development of Domino Card Media in IPAS to Improve Learning Outcomes Students of SD Negeri Patemon 02 Gunung Pati District, Semarang City - Yusrika Anabella; Desi Wulandari (Postgraduate, University of Mataram, 2024)
One of the most important elements in educational activities is the learning media. But in practice, only a few teachers are able to take advantage of the learning media that exist today, this has an impact on student learning outcomes. Therefore, the purpose of this study was to develop domino cards as a learning media teaching science in elementary schools. This research uses the Research and Development method with the model used. namely Borg and Gall. This study involved teachers and 20 students in grade V of SD Negeri Patemon 02. Domino learning media was designed to meet the needs of teachers and students through documentation, interviews, observations, and questionnaires. The study results show the percentage of level of eligibility of domino card media by material and media experts with a percentage of 95% and 93% respectively with very feasible criteria. The pretest and posttest results show that domino card learning media improves student learning outcomes, with an n-gain value of 0.55 and moderate criteria. This shows that domino card learning media is effective for improving student learning outcomes science learning outcomes in learning grade V students of SD Negeri Patemon 02 human respiratory system material.